Perspectives on strategies for improving ultra-deep desulfurization of liquid fuels through hydrotreatment: Catalyst improvement and feedstock pre-treatment - Dembaremba, Tendai O.; Majodina, Siphumelele; Walmsley, Ryan S.; Ogunlaja, Adeniyi S.; Tshentu, Zenixole R. (Frontiers in Chemistry, 2022)
Reliance on crude oil remains high while the transition to green and renewable sources of fuel is still slow. Developing and strengthening strategies for reducing sulfur emissions from crude oil is therefore imperative and makes it possible to sustainably meet stringent regulatory sulfur level legislations in end-user liquid fuels (mostly less than 10 ppm). The burden of achieving these ultra-low sulfur levels has been passed to fuel refiners who are battling to achieve ultra-deep desulfurization through conventional hydroprocessing technologies. Removal of refractory sulfur-containing compounds has been cited as the main challenge due to several limitations with the current hydroprocessing catalysts. The inhibitory effects of nitrogen-containing compounds (especially the basic ones) is one of the major concerns. Several advances have been made to develop better strategies for achieving ultra-deep desulfurization and these include: improving hydroprocessing infrastructure, improving hydroprocessing catalysts, having additional steps for removing refractory sulfur-containing compounds and improving the quality of feedstocks. Herein, we provide perspectives that emphasize the importance of further developing hydroprocessing catalysts and pre-treating feedstocks to remove nitrogen-containing compounds prior to hydroprocessing as promising strategies for sustainably achieving ultra-deep hydroprocessing.